Does the Inclusion of Second Generation Genetically Modified Plants in Feeds have any effect on Animal Performance? - Jacob Matovu (Turkish Journal of Agriculture: Food Science and Technology)
The need for studies on the nutritional value of plants depends on their composition. The first generation genetically modified Plants (GMPs) have the same composition as their near-isogenic lines. Therefore, they have the same nutritional value, and most of the animal feeding studies have found no significant differences in the production and health parameters of animals that consumed first-generation GMPs in comparison to non-GMPs. Due to the recent production of transgenic plants with specific nutritional properties (second generation GMPs), their use as feed for animals is viewed with skepticism in very many countries. In this critical review, it is concluded that most of these nutritionally improved plants have not shown adverse effects on the performance of various animals compared to their near-isogenic lines and can therefore be considered in the animal feed industry. However, most of the experiments were conducted on laboratory animals. There is a need to conduct them with animals that are mainly consumed by humans, such as ruminants. There is also a need to feed the whole plant to these animals and not just certain parts of the plant to get a clear picture of its overall safety. In addition, there is a need to determine a suitable long-term nutritional and toxicological approach assessment.